2021
DOI: 10.3390/s21061973
|View full text |Cite
|
Sign up to set email alerts
|

Near-Field Vortex Beams Diffraction on Surface Micro-Defects and Diffractive Axicons for Polarization State Recognition

Abstract: The diffraction of vortex Gaussian laser beams by elementary objects of micro-optics (surface micro-defects) to recognize the type of polarization (linear, circular, radial, azimuthal) of the input radiation was investigated in this paper. We considered two main types of defects (protrusion and depression in the form of a circle and a square) with different sizes (the radius and height were varied). Light propagation (3D) through the proposed micro-defects was modeled using the finite difference time domain (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 70 publications
0
6
0
2
Order By: Relevance
“…The results are shown in figure 3. As previously shown 32,42 , the following is true for optical vortices of the first order: a zero value of the central focal spot indicates "+" circular polarization, and a nonzero one indicates "-" circular polarization. Similarly, for radial polarization there will be a zero value at the central focal point, and a non-zero value means azimuthal polarization 42 .…”
Section: The Investigation Laguerre-supergauss (10) Modes Diffraction...mentioning
confidence: 63%
See 1 more Smart Citation
“…The results are shown in figure 3. As previously shown 32,42 , the following is true for optical vortices of the first order: a zero value of the central focal spot indicates "+" circular polarization, and a nonzero one indicates "-" circular polarization. Similarly, for radial polarization there will be a zero value at the central focal point, and a non-zero value means azimuthal polarization 42 .…”
Section: The Investigation Laguerre-supergauss (10) Modes Diffraction...mentioning
confidence: 63%
“…Previous studies have shown that under certain conditions, a conventional round protrusion can be used to recognize polarization and focusing, and the focusing will be better than for a diffractive axicon with a similar grating size 32,43 . But the relief height also plays a key role 44,45 .…”
Section: The Investigation Laguerre-supergauss (10) Modes Diffraction...mentioning
confidence: 99%
“…При таком типе круговой поляризации, как было показано ранее [13,39], наблюдается перераспределение энергии между компонентами электромагнитного поля, выраженное в усилении продольной компоненты электрического поля на оптической оси.…”
Section: исследование дифракции супер-гауссова пучка на кольцевых реш...unclassified
“…Для формирования протяженного светового отрезка вдоль оптической оси достаточно часто используются аксиконы [34 -38], в том числе их дифракционные аналоги (кольцевые решетки) [39,40]. Изменение высоты рельефа оптического элемента существенным образом влияет на картину дифракции лазерного излучения [36, 39 -42].…”
Section: Introductionunclassified
“…With the development of the electronic industry, sensors have become more important than ever before. Large numbers of sensors work in narrow bandpass circumstances or individual frequency [1,2]. Although the finite-difference time-domain (FDTD) algorithm has been extensively employed in many applications, sensor simulation by the FDTD algorithm is severely limited by the inefficient bandpass calculation.…”
Section: Introductionmentioning
confidence: 99%